Z prawnej problematyki jakości produktów rolnictwa ekologicznego - Leśkiewicz, Katarzyna (Wydawnictwo Naukowe UAM, 2007)
The objective of the paper is to define legal elements of organic agricultural products quality. The quality of organic agricultural products is a specific category of agricultural products quality. According to Community regulations the quality of organic agricultural products is placed in the "quality of production" system in accordance with the standards set out by the Council Regulation (EEC) No 2092/91 of 24 July 1991. The quality of organic agricultural products is not of local character, but comes under globalisation and is subject to standards that serve the liberalisation of trade, contrary to ‘agricultural products as traditional specialties guaranteed’, ‘products with designation of origin’, or ‘products with geographical indications’. The quality of organic agricultural products derives from the quality of the organic method, whose compliance with the prescribed standards, and the requirements of Regulation No 2092/91 is subjected to inspection proceedings during all stages of production and marketing. The competent authority then confirms positive effects of such proceedings with a certificate of inspection stating the compliance with those standards, which is notified to consumers by an organic label on agricultural products.
FROM THE LEGAL ISSUES OF THE QUALITY OF ORGANIC AGRICULTURAL PRODUCTS